The effect of inflation on the formulation of monetary policy in Iraq - Mahmoud Mohamed, Al-Daghir,; Qasim Hashim, Suad; Hameed Mutlag, Haitham (Opción, 2020)
The research attempted to diagnose the relationship between inflation and the exchange rate and its realistic significance in formulating the goal of stability in growth rates for the general level of prices, by regulating the money supply flows within the framework of the central bank's management of the purchasing power of the Iraqi dinar through its cash operations in organizing the movement of the monetary basis to reach actual inflation within the target. The research reached the efficiency of the exchange rate, a nominal anchor of monetary policy.